2022
DOI: 10.1177/10760296211073767
|View full text |Cite
|
Sign up to set email alerts
|

A New Score for Determining Thrombus Burden in STEMI Patients: The MAPH Score

Abstract: Aim to investigate whether the MAPH score, which is a new score that combines blood viscosity biomarkers such as mean platelet volume (MPV), total protein and hematocrit, can be used to predict thrombus burden in ST-segment elevation myocardial infarction (STEMI) patients. Methods A total of 473 consecutive patients with STEMI were included in the study. Intracoronary tirofiban/abciximab infusion was applied to patients with thrombus load ≥3 and these patients (n = 71) were defined as the patient group with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Recently, the MAPH score, incorporating age and MPV parameters in addition to the components of LSR and HSR, has been introduced as a new index for blood viscosity. 15 It has been associated with a high thrombus burden in patients with both ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction. 14, 15 In a study involving 260 patients who underwent primary percutaneous coronary intervention and had TIMI 0 flow, it was reported that the MAPH score predicted the presence of TIMI coronary flow after stent implantation with 78% specificity and 45% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the MAPH score, incorporating age and MPV parameters in addition to the components of LSR and HSR, has been introduced as a new index for blood viscosity. 15 It has been associated with a high thrombus burden in patients with both ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction. 14, 15 In a study involving 260 patients who underwent primary percutaneous coronary intervention and had TIMI 0 flow, it was reported that the MAPH score predicted the presence of TIMI coronary flow after stent implantation with 78% specificity and 45% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been associated with a high thrombus burden in patients with both ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction. 14, 15 In a study involving 260 patients who underwent primary percutaneous coronary intervention and had TIMI 0 flow, it was reported that the MAPH score predicted the presence of TIMI coronary flow after stent implantation with 78% specificity and 45% sensitivity. 42 In addition to these cohorts as a consequence of atherosclerosis, the predictive role of the MAPH score has also been investigated in patients with CSFP, which is a distinct angiographic clinical entity characterized by delayed coronary opacification in the absence of significant obstructive CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Abacıoğlu et al reported that the MAPH score estimated the thrombus burden in patients with STEMI. In their paper, MPV levels and age were included in the calculation of MAPH score, in addition to total protein and haematocrit [4]. Abacıoğlu et al 's [4] pioneering research found a relationship between blood viscosity and an HTB using the MAPH score in STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off levels for MPV, age, total protein and haematocrit were calculated according to the Youden index for HTB. Levels higher than the cut-off were accepted as a score of 1, and MAPH score was evaluated accordingly [4].…”
Section: Laboratory Measurementsmentioning
confidence: 99%
See 1 more Smart Citation